Towards Effective ‘Almajiri’ and Nomadic Education for Sustainable Development in Nigeria - Adeniyi - Egbeola, Folakemi Oyeyemi (NIU Journal of Humanities, 2018)
Education, as a continuous process of refinement, requires the combined efforts of all the stakeholders in the society to provide the platform that will bring about so much desired value education to minimize the current high spate of tension and violence all over the world. The current ‘Boko Haram’ insurgency and constant attack of the Fulani herdsmen in Nigeria which has made the entire country especially the north to be in a terror siege stemmed from the high level of poverty suffered by such groups as ‘Almajiri’ and nomadic children. They constitute 70% street children in Nigeria. For the country to achieve the Millennium Development Goals (MDGS) and Education for All (EFA), the Federal Government set up the ministerial committee to find out how these out- of- school children can be properly integrated into the UBE Scheme. Based on their findings, Government has embarked on some laudable efforts. The focus of this paper therefore is to suggest ways to improve on government efforts especially in the areas of teacher preparation, adaptation of curriculum and teaching materials that can enhance the desired effective education needed for sustainable development.  Keywords : Almajiri and Nomadic education, materials adaptation, curriculum adaptation and teacher preparation